Cartografia de itinerários de cuidado de saúde mental em uma cidade da 6ª Regional de saúde do Paraná - Souza, Fabíola Ferreira de (2018)
The Psychiatric Reform, under the bias of deinstitutionalization, proposes a paradigm shift in relation to the phenomenon of madness, in which the subject ceases to be reduced to the disease and begins to be considered in a complex and integral perspective. In view of this, it is proposed to diversify care strategies and attention points, opening the possibility of composing different pathways in the constitution of care. The work aims to compose a map of the therapeutic itineraries of users of the mental health network of a city of the 6th Regional Health of Paraná through narratives. It is a cartography, using as devices for the production of the data the interviews and the construction of the research diary. Five selected participants were interviewed together with the teams of five Family Health Strategies - ESF that make up the municipality. The chosen participants had severe psychic suffering and were cases that the teams identified as complex, mobilizing the teams. The analysis of implication in the process constituted as an important tool of analysis, considering that the researcher is also a field psychology technician. We could observe the role of the therapeutic itinerary as a possibility to draw the subject's path in the mental health network from experience. We observed that although public policy brings the proposal of a model of community-based care, the subjects' experiences are strongly marked by psychiatric hospitalization. The therapeutic itineraries allowed reflections on the possibilities of care in the networks, access barriers, the directions of the psychiatric reform and specificities of Paraná. Reflecting the importance of the Psychiatric Reform in culture, from the public policies to the ways of producing health in the informal networks of the subjects. The tool made it possible to analyze the challenges and potentialities of the care offered and produced in the networks. We affirm the importance of thinking about the impacts of care models on the subjects with psychic suffering, considering the political changes in mental health and the Unified Health System - SUS in Brazil.